2017
DOI: 10.1128/aac.01845-16
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Vancomycin MIC on Treatment Outcomes in Invasive Staphylococcus aureus Infections

Abstract: There are conflicting data on the association of vancomycin MIC (VAN-MIC) with treatment outcomes in Staphylococcus aureus infections. We investigated the relationship between high VAN-MIC and 30-day mortality and identified the risk factors for mortality in a large cohort of patients with invasive S. aureus (ISA) infections, defined as the isolation of S. aureus from a normally sterile site. Over a 2-year period, 1,027 adult patients with ISA infections were enrolled in 10 hospitals, including 673 (66%) patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…Although previous studies have stated that E-tests over estimated high vancomycin MICs and Vitek II might fail to detect vancomycin MIC elevation (Swenson et al, 2009;Bloomgren & Laible, 2013;Tomczak et al, 2013), our results revealed that the E-test derived MICs were highly consistent with those provided by broth microdilution. This finding is in line with recent studies (Van Hal et al, 2011;Song et al, 2017). Likewise, Hsu et al (2008) suggested that MICs derived by E-tests were more reflective of the prognosis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although previous studies have stated that E-tests over estimated high vancomycin MICs and Vitek II might fail to detect vancomycin MIC elevation (Swenson et al, 2009;Bloomgren & Laible, 2013;Tomczak et al, 2013), our results revealed that the E-test derived MICs were highly consistent with those provided by broth microdilution. This finding is in line with recent studies (Van Hal et al, 2011;Song et al, 2017). Likewise, Hsu et al (2008) suggested that MICs derived by E-tests were more reflective of the prognosis.…”
Section: Discussionsupporting
confidence: 90%
“…The literature contains conflicting data regarding whether MRSA-vancomycin MICs could actually reflect the prognosis. Some studies have suggested that vancomycin MICs enabled the determination of adverse clinical outcomes (Honda et al, 2011;Han et al, 2012;Rojas et al, 2012;Hope et al, 2013), whereas others have not (Hos et al, 2017;Song et al, 2017;Adani et al, 2018;Bouiller et al, 2018). Because the MIC-guided treatment decision is controversial in low MRSA-vancomycin MICs (≤2 µg/mL), the IDSA also recommends that the actual clinical and microbiological response should be considered as a guide to treatment decisions if the MRSA-vancomycin MIC is low (Liu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A higher vancomycin and teicoplanin MIC of ≥ 1.5 μg/ml has been linked to poor clinical outcomes in patients with MRSA bacteremia [57]. In recent years, heterogeneous vancomycin-intermediate S .…”
Section: Introductionmentioning
confidence: 99%
“…There are con icting data with regard to the association between treatment failure and an MIC of 1.5 mg/L or greater. [18,19,31,32] This study demonstrated no association between mortality and an MIC of 1.5 mg/L or greater. Given a vancomycin MIC of ≤ 1.5 mg/L, vancomycin is still a mainstay of treatment for MRSA infection in our hospital.…”
Section: Discussionmentioning
confidence: 46%